Combined Delivery of Consolidating Pulps to the Remote Sites of Deposits - Golik, V.I.; Efremenkov, Andrey Borisovich (IOP Publishing, 2017)
The problems of modern mining production include limitation of the scope of application of environmental and resource-saving technologies with application of consolidating pulps when developing the sites of the ore field remote from the stowing complexes which leads to the significant reduction of the performance indicators of underground mining of metallic ores. Experimental approach to the problem solution is characterized by the proof of technological capability and efficiency of the combined vibration-pneumatic-gravity-flowing method of pulps delivery at the distance exceeding the capacity of current delivery methods as it studies the vibration phenomenon in industrial special structure pipeline. The results of the full-scale experiment confirm the theoretical calculations of the capability of consolidating stowing delivery of common composition at the distance exceeding the capacity of usual pneumatic-gravity-flowing delivery method due to reduction of the friction-induced resistance of the consolidating stowing to the movement along the pipeline. The parameters of the interaction of the consolidating stowing components improve in the process of its delivery via the pipeline resulting in the stowing strength increase, completeness of subsurface use improves, the land is saved for agricultural application and the environmental stress is relieved.
Keywords: горное производство; ресурсосберегающие технологии; целлюлоза; подземная добыча; металлические руды; трубопроводы; рудные поля; вибрации